Determinants of Organizational Performance of Select Thrift Banks - Ramirez, Jess Mar D.; Montecillo, Marichu B. (Future Science / FSH-PH Publications, 2022)
The impact of organizational performance plays a vital role in propelling both economy and stability. Over the years banks have been aggressive in expansion and merging to maximize their market presence in the country. And they have become interested in determining what factors affect organizational performance and what appropriate strategies to make in order to achieve productivity and profitability. This study investigated the influence of perceived organizational culture, job satisfaction, service quality, and organizational performance among clients and employees in thrift bank basis as for strategy enhancement. It was conducted among the four thrift banking institutions in the Province of Bukidnon, Northern Mindanao, Philippines. Quantitative descriptive research method was employed, four (4) survey questionnaires were the main data gathering tools complemented with key informant’ interview to substantiate the result. Descriptive statistics, Pearson (r) and multiple linear regressions were used to organize the data. The result of the study showed that there is significant relationship between the organizational culture, service quality and organizational performance. However, job satisfaction appears to have no significant influence on the organizational performance. The study concluded that the higher level of service quality and strong organizational culture have significant influence to organizational performance.